Preschool Children Science Mental Representations: The Sound in Space - Konstantinos Ravanis; George Kaliampos; Panagiotis Pantidos (MDPI AG, 2021)
The aim of the current study was to examine the way in which preschool children deal with the concept of sound. For this purpose, a study was carried out in the context of detecting and categorizing the mental representations among young children of sounds which propagate through space from source to the receiver. Specifically, 91 preschool children aged 5-6 years voluntarily participated in individual semi-structured interviews which were carried out by three researchers in a special area of kindergartens. During these interviews, the children were asked to express their views on the three following axes: the concept of sound itself; the subjective characteristics of sound; and the phenomenon of the production and propagation of sound. The results of the research showed that while a small percentage of children recognized the propagation of sound in space, the vast majority of them associated sound with either the object that produced it or with the object that received it.